Efektivitas Media Video Animasi, Leaflet Dan Metode Demonstrasi Dalam Meningkatkan Pengetahuan Cuci Tangan Pakai Sabun Pada Siswa Sekolah Dasar Inpres Laloasa, Kabupaten.Gowa - Rasjid, Ashari; Khaer, Ain; Handayani, Nur (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
Handwashing is a positive behavior that should be taught to children in elementary schools to maintain cleanliness and avoid various health problems that may arise. Therefore, it is crucial to convey health information to elementary school students through animated videos, brochures, and demonstration methods. This study aims to evaluate the effectiveness of animated videos, brochures, and demonstration methods in increasing knowledge about Handwashing with Soap among students of SD Inpres Laloasa, Gowa Regency. The type of research conducted was an analytical observational study with a quasi-experimental approach using a pre-test and post-test design in one group. The sampling method applied was purposive sampling with a total of 96 respondents, which were then analyzed using the Mc. Nemar test. The findings of the study with the application of the Mc. Nemar test showed that animated videos can increase knowledge about CTPS with an increase of 56.3% and p = 0.001. In addition, pamphlets as a medium were proven effective in increasing understanding of CTPS with a percentage increase reaching 43.7% and p = 0.001. The demonstration method also demonstrated success in improving understanding of CTPS with a 50% increase and p = 0.001. The results of this study indicate that animated videos, brochures, and demonstration techniques are efficient methods for improving understanding of CTPS among elementary school students. It is hoped that effective health promotion techniques and methods can be implemented to broaden students' knowledge.